2013
DOI: 10.1071/ch12365
|View full text |Cite
|
Sign up to set email alerts
|

Flow Microwave Technology and Microreactors in Synthesis

Abstract: A bespoke microwave reactor with a glass containment cell has been developed for performing continuous flow reactions under microwave heating. The prototype unit has been evaluated using a series of standard organic chemical transformations enabling scale-up of these chemical processes. As part of the development, a carbon-doped PTFE reactor insert was utilized to allow the heating of poorly absorbing reaction media, increasing the range of solvents and scope of reactions that can be performed in the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Furthermore, this reaction has been studied in a conductive heating Uniqsis FlowSyn reactor [71,73] and its comparison with microwave heating batch experiments showed that the energy efficiency of these technology platforms vary with scale, but broadly are comparable [73]. Furthermore, recently a bespoke microwave reactor with a glass containment cell has been used under continuous flow processing for 4-component Hantzsch DHP synthesis in good yield [74]. Given this precedent and our own previous studies on the use of microwave irradiation in a single-mode instrument to promote 4-component DHP synthesis [70], this reaction seemed ideal to expand the scope of the microwave flow cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this reaction has been studied in a conductive heating Uniqsis FlowSyn reactor [71,73] and its comparison with microwave heating batch experiments showed that the energy efficiency of these technology platforms vary with scale, but broadly are comparable [73]. Furthermore, recently a bespoke microwave reactor with a glass containment cell has been used under continuous flow processing for 4-component Hantzsch DHP synthesis in good yield [74]. Given this precedent and our own previous studies on the use of microwave irradiation in a single-mode instrument to promote 4-component DHP synthesis [70], this reaction seemed ideal to expand the scope of the microwave flow cell.…”
Section: Resultsmentioning
confidence: 99%
“…81% yield of a DHP under flow processing [74], 51–92% yield [67] or 84–99% yield [72] of a range of derivatives in batch using a single-mode instrument, and 96% yield of 15a under open vessel batch conditions on 0.5 mol scale [10]) and transfers well to flow processing giving 85% yield under microwave irradiation (cf. 81% [74]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…70,104 The combination of multiple, differently functionalized scavenger resins is a common practice for the removal of several different impurities. 44,66,33,102,[105][106][107] In an illustrative example, removal of homogeneous transition metal complexes was possible this way ( Fig. 17), which prevented harmful catalytic activity in downstream heterogeneous nitro group reductions in the flow synthesis of the fungicide Boscalid Ò .…”
Section: In-line Work-upmentioning
confidence: 99%
“…The topics range from new applications of flow photochemistry, [3,4] complex multi-step synthesis, [5,6] and the development of novel supported reagents, to microreactors and innovative methods for in-line analysis and real-time monitoring. [7][8][9] The field is now moving beyond demonstrating the adaptation of known chemical transformations to continuous flow, to embarking on the exploration of new reaction space. Applications involving the safe generation of hazardous reagents or reactive intermediates in microreactors are reported herein.…”
mentioning
confidence: 99%